Geometry of Middle to Late Triassic extensional deformation pattern in the Cordillera del Viento (Southern Central Andes): A combined field and geophysical study - Sagripanti, L.; Folguera, A.; Giménez, M.; Rojas Vera, E. A.; Fabiano, J. J.; Molnar, N.; Fennell, L.; Ramos, Víctor A. (Journal of Iberian Geology, 2014)
Combined field and gravimetric-magnetic data reveal a complex pattern of extensional structures superimposed to the late Carboniferous – Early Permian Gondwanan orogen at the inner sectors of the Southern Central Andes, in the westernmost part of the Chos Malal fold and thrust belt at the cordillera del Viento area. W-NW, NW basement structures of regional significance, segmented by minor NE structures are bounding Late Triassic depocenters and structural highs corresponding to the cordillera del Viento rifting, equivalent to the Precuyo cycle. A pattern of roughly N-S trending structures recognized in the field associated with Andean thrusts do not show evidences of previous structural controls, as they cut the magnetic anomalies. Field observations show that W-NW, NW and NE normal structures control changes in Late Triassic sedimentary thicknesses and are associated with synextensional geometries. Our model indicates that Late Triassic rifting in the area would have had a regional W-NW to NW trend being segmented by minor NE structures. Both sets were reactivated during Andean times, acting W-NW and NW structures as transfer zones between decoupled contractional panels and NE structures as frontal contractional structures. N-S contractional structures did not respect rifting architecture cutting through the depocenters and occasionaly exhuming synextensional geometries.